2019
DOI: 10.1108/ijtc-04-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Overtourism and the night-time economy: a case study of Budapest

Abstract: Purpose The purpose of this paper is to analyse the phenomenon of overtourism with specific reference to the night-time economy (NTE) in Budapest, Hungary. Design/methodology/approach The research took place between September and December 2017 in the so-called “party quarter” of Budapest – District VII. The chosen methods included mapping, observation, interviews and questionnaires with local residents, visitors and tourists. Findings Partying opportunities are valued highly by tourists and the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
78
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 31 publications
1
78
0
8
Order By: Relevance
“…Just as studies of the urban night have overly fixated on traditional (hedonistic) nightlife, studies of tourism at night have also tended to focus on established night-time activities: drinking, eating, theatre, and other forms of entertainment. There has been some attention dedicated to the rising popularity of night markets, particularly in Asia (Hsieh & Chang, 2006;Lee, Chang, Hou, & Lin, 2008), and there is a substantial body of work on other activities associated with the night and tourism, such as alcotourism and sex-tourism (Bell, 2008;Pinke-Sziva, Smith, Olt, & Berezvai, 2019;Sanders, 2017;Thurnell-Read, 2012) . Since the 1990s there has also been academic recognition of tourist-oriented occasions such as hen and stag parties, music events, and other festivals typically occurring in the night (Smith, 2016).…”
Section: Night-time Tourismmentioning
confidence: 99%
“…Just as studies of the urban night have overly fixated on traditional (hedonistic) nightlife, studies of tourism at night have also tended to focus on established night-time activities: drinking, eating, theatre, and other forms of entertainment. There has been some attention dedicated to the rising popularity of night markets, particularly in Asia (Hsieh & Chang, 2006;Lee, Chang, Hou, & Lin, 2008), and there is a substantial body of work on other activities associated with the night and tourism, such as alcotourism and sex-tourism (Bell, 2008;Pinke-Sziva, Smith, Olt, & Berezvai, 2019;Sanders, 2017;Thurnell-Read, 2012) . Since the 1990s there has also been academic recognition of tourist-oriented occasions such as hen and stag parties, music events, and other festivals typically occurring in the night (Smith, 2016).…”
Section: Night-time Tourismmentioning
confidence: 99%
“…Thus, the externalities resulting from the SE in (over)tourism context on the community level could be a laboratory for SE's influence in general.Although sustainability issues involving the SE have been discussed quite often in the tourism development context [1,24,26,29], these studies were contextual, based on the case studies, and also related to various conceptual frameworks(or none, if not indicated by the authors). The majority of them identify and characterize the positive/negative impact of the SE on local communities by referring to respondents' opinions or figures indicating a certain stage or level of the phenomenon [3,4,30,31]. Theoretical studies investigating the process of the SE impact itself through the prism of concrete theoretical frameworks can hardly be found.…”
mentioning
confidence: 99%
“…The other works are based on tourism-specific concepts: tourism degrowth theories [42], the social carrying capacity concept [4], Doxey's [43] Irridex model and Butler's [44] Tourism Areal Life Cycle Model. Alternatively, they design their own research frameworks [25,30,45]. Two literature reviews conclude the set of literature.Moreover, in the conclusion part, we used more general literature referring to both tourism development and social capital.…”
mentioning
confidence: 99%
“…Maybe, though this is perhaps particularly applicable to some of the earlier models in the smart cities longitudinal spectrum. In fact, there is growing consensus around the fact that technological innovation (Pinke-Sziva et al, 2019;Skeli and Schmid, 2019) can alleviate some of the effects of overtourism, particularly in the context of smart tourism destinations (Gretzel and Scarpino-Johns, 2018). This includes 'smarter' transport solutions, even if we know that residents and tourists will differ considerably in their assessment of urban mobility improvements (Albalate and Bel, 2010).…”
mentioning
confidence: 99%